Gravity Stress Radiographs and the Effect of Ankle Position on Deltoid Ligament Integrity and Medial Clear Space Measurements. (May 2017) - Ashraf, Ali; Murphree, Jacob; Wait, Eric; Winston, Travis; Wooldridge, Adam; Meriwether, Matthew; Wilson, Joshua; Grimes, Jerry S.
Abstract : Introduction: External rotation and gravity stress radiographs have been described to distinguish stable supination-external rotation-II (SER-II) ankle fractures from unstable SER-IV fractures. It has been previously shown that both external rotation and gravity stress views are equivalent in their ability to diagnose deltoid ligament injury. It has also been shown that the position of the ankle influences the external rotation stress radiograph. However, no data of ankle position exist for gravity stress radiographs. Methods: Eight fresh-frozen cadaveric ankles were dissected and destabilized sequentially according to the SER mechanism of ankle fractures, starting with the anterior inferior tibiofibular ligament, distal fibula osteotomy at the level of the syndesmosis, posterior inferior tibiofibular ligament, superficial deltoid ligament, and finally the deep deltoid ligament. Fluoroscopic radiographs were taken with gravity stress views in both neutral and plantarflexion. Measurements of both dorsal and the medial clear space were taken for each stage. The difference between the dorsal and medial clear space was measured. Results: Positive predictive value (PPV) with a medial clear space cutoff of 5 mm was 80% in plantarflexion and 72.72% in neutral with a negative predictive value (NPV) of 100% in both positions. Using a 6-mm cutoff, the PPV improved to 100% and NPV remained 100% for both neutral and plantarflexion. When the difference measurement is used, a 1.0-mm difference yielded a PPV of 72% and an NPV of 100% in both neutral and plantarflexion. With a 1.5-mm cutoff, the PPV and NPV were 100% for both positions. Conclusions: The position of the ankle during gravity stress radiographs does not influence the clinical effectiveness of the images. Using larger references for stability, the PPV can be improved.